225Ac-Prostate-Specific Membrane Antigen Therapy for Castration-Resistant Prostate Cancer: A Single-Center Experience. (29th December 2021) - Sanli, Yasemin; Kuyumcu, Serkan; Simsek, Duygu Has; Büyükkaya, Fikret; Civan, Caner; Isik, Emine Goknur; Ozkan, Zeynep Gozde; Basaran, Mert; Sanli, Oner
Abstract : Purpose: Prostate-specific membrane antigen (PSMA)–targeted therapies are among the current promising treatments. We present our preliminary results on the use of 225 Ac-PSMA therapy in patients with metastatic castration-resistant prostate cancer as a single center. Methods: Twelve advanced stage metastatic castration-resistant prostate cancer patients who received 225 Ac-PSMA therapy were recruited in this retrospective study. Patients were treated with 225 Ac-PSMA therapy every 8 weeks, and prostate-specific antigen (PSA) response was analyzed. Meanwhile, overall survival (OS) and progression-free survival (PFS) were estimated. Hematological and nonhematological adverse effects were recorded before and at 8 weeks after the last treatment cycle. Results: In total, 25 cycles of 225 Ac-PSMA were administered to 12 patients. The pretreatment median PSA level was 129 ng/mL. After the first cycle of therapy, any PSA response was observed in 9 of 12 patients, whereas 6 of them had biochemical response of >50%. Four of 12 patients reached the best PSA response after the first treatment cycle, whereas 3 patients after the second and 2 patients after the third cycle. The median PFS and OS were 4 and 10 months, respectively. For patients with any PSA response after the first cycle, OS was found to be higher despite without any statistical significance (10 vs 4 months; P = 0.301) when compared with the nonresponsive group. No significant difference was encountered in terms of adverse effect in the pretreatment and posttreatment era. Conclusions: Our preliminary results are encouraging, especially patients who had PSA response after the first cycle of 225 Ac-PSMA therapy.